Review of the Method of Valuation of the SDR : Amendment to Rule O-1. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This paper seeks Executive Board approval of an amendment to Rule O-1, which specifies the currency amounts in the SDR valuation basket.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Executive Board Approval; PP; SDR; Value Of The SDR; Value; United States